SOCIALIZATION OF ONLINE PASSPORT QUEUE REGISTRATION (APAPO) AND EAZY PASSPORT APPLICATIONS BY TARUNA AND EMPLOYEES OF IMMIGRATION OFFICE CLASS I BORDER CONTROL LAMPUNG - Mutia Amalia Azmy; Intan Nurkumalawati (Polteknik Imigrasi, 2021)
Immigration polytechnic cadets have the obligation to carry out community service, this is in accordance with the Tri Dharma of Higher Education in the third point. As a form of this service, the Immigration Polytechnic cadets together with immigration officers carry out outreach activities to the public regarding Eazy Passport and the Online Passport Queue Registration (APAPO) application. and efficient.